Penggunaan Student Teams Achievement Division untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Materi Konsep Persamaan Dasar Akuntansi - Basuki Basuki Darsono (Balai Diklat Keagamaan Semarang, 2023)
This study aims to increase the activeness and learning outcomes of students in the concept of basic accounting equations. The research subjects were students of class XII IPS-1 MAN 2 Rembang who were taught using the Student Teams Achievement Division (STAD) Model. The instruments used are in the form of observation sheets and tests. The research method using CAR includes four stages, namely planning, implementation, observation, and reflection. The strategy used is related to the Student Teams Achievement Division (STAD) model, dividing the class into several learning teams based on gender, race and low, average, and high achievement. This research was conducted in two cycles. The results of the Student Teams Achievement Division (STAD) strategy research can increase activeness and learning outcomes. High activity data analysis, 10% initial condition, first cycle 28.5% and second cycle 52.8%. Analysis of learning outcomes data showed an increase from the initial condition 31% (low), the first cycle 61% (moderate), and the second cycle rose 78% (high). Thus, this strategy is considered successful because the 78% completeness exceeds the 75% success criteria.